Decision-making fusion of InSAR technology and offset tracking to study the deformation of large gradients in mining areas-Xuemiaotan mine as an example - Ma, Jianquan; Yang, Juncheng; Zhu, Zhanrong; Cao, Husheng; Li, Shibo; Du, Xiaolan (Frontiers in Earth Science, 2022)
In view of the intense surface subsidence caused by underground coal mining, the subsidence has the characteristics of large settlement magnitude and severe deformation. However, it is very challenging to monitor this process by using the traditional interferometric synthetic aperture radar (InSAR) method. Therefore, based on 15 Sentinel-1A image data, 30302 working faces of the Xuemiaotan mining area in Yulin City, Shaanxi Province were provided in this work as an example to propose the implementation of the small baseline subset interferometric synthetic aperture radar (SBAS-InSAR), continuous D-InSAR and the offset-tracking technology integration methods. More specifically, the continuous D-InSAR technology and SBAS-InSAR technology were used to monitor the small deformation in the edge area of the subsidence basin, while the offset-tracking technology was used to monitor the large gradient deformation in the centre of the subsidence basin. By leveraging from the advantages of these three methods and overcoming the shortcomings of each method, the three-deformation information process was fused, and the complete deformation law of the whole goaf surface was obtained. The acquired results show that the outcomes of the fusion method are consistent with the measured data, whereas the root mean square error of the vertical displacement (RMSE) was 11 cm, and the average absolute error (MAE) was 7 cm. This fusion of the SBAS-InSAR, continuous D-InSAR, and offset-tracking technologies provides a new idea for monitoring a large gradient deformation of mining subsidence.